DAMPAK ALIH FUNGSI LAHAN PERTANIAN DI DAERAH IRIGASI KEDUNGGUPIT KABUPATEN KUDUS - , HARRY WIBOWO; , Ir. Suryanto, MSP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The phenomena of farm land conversion, especially technical irrigation land, indicated that land use change is becoming more intensive because of the local economy development. This research aims to find impacts of farming land conversion in Kedunggupit Irrigation Area, Kudus Regency. The method used in this research as deductive-explorative method using descriptive-qualitative analysis. The results of the research shows that farming land conversion rate in Kedunggupit Irrigation Area, Kudus Regency has increased from 1990 to 2005 with averagely -3.07%/year